Negotiations between health and social goals over the lifespan: The role of future time perspective. (August 2019) - Li, Kin-Kit
The interplay between health and social goals in relation to age and future time perspective was examined among 131 older and 131 younger adults via surveys and future time manipulations (limited, unchanged, and expansive). Being older was associated with weaker physical activity intentions and social activity intentions as mediated by a limited future time perspective. Physical activity intentions decreased in the limited condition and increased in the expansive condition, social activity intentions increased in all conditions, and preference toward health (over social) goals decreased in both the limited and expansive conditions. The results suggest that anticipated endings may become salient in all conditions and favor social goals, which are emotionally relevant.